Anaerobic digestion challenges and resource recovery opportunities from land-based aquaculture waste and seafood processing byproducts: A review. (June 2022) - Choudhury, Abhinav; Lepine, Christine; Witarsa, Freddy; Good, Christopher
Graphical abstract: Highlights: Anaerobic digestion (AD) may be suitable to treat aquaculture and fishery wastes. Challenges to valorization of aquaculture and fishery wastes via AD are analyzed. Major inhibitory concerns are elevated LCFA, ammonia, salinity, and low alkalinity. Recovery opportunities for valuable biomolecules and nutrients are highlighted. Future research for implementation of AD in the fishery industry is discussed. Abstract: The unprecedented demand for seafood has resulted in land-based recirculating aquaculture systems (RAS), a highly intensive but sustainable fish farming method. However, intensification also results in concentrated waste streams of fecal matter and uneaten feed. Harvesting and processing vast quantities of fish also leads to the production of byproducts, further creating disposal challenges for fish farms. Recent research indicates that anaerobic digestion (AD), often used for waste treatment in agricultural and wastewater industries, may provide a viable solution. Limited research on AD of freshwater, brackish, and saline wastewater from RAS facilities and co-digestion of seafood byproducts has shown promising results but with considerable operational and process stability issues. This review discusses challenges to AD due to low solid concentrations, salinity, low carbon/nitrogen ratio, and high lipid content in the waste streams. Opportunities for recovering valuable biomolecules and nutrients through microbial treatment, aquaponics, microalgae, and polyhydroxyalkanoate production are also discussed.